Histopathological characteristics of subsequent melanomas in patients with multiple primary melanomas. (6th December 2012) - Vecchiato, A.; Pasquali, S.; Menin, C.; Montesco, M.C.; Alaibac, M.; Mocellin, S.; Campana, L.G.; Nitti, D.; Rossi, C.R.
Abstract Background Multiple primary melanomas (MPM) occur in up to 20% of melanoma patients, and subsequent tumours seem to have a favourable histopathological pattern. Objective A prospectively collected cohort of 194 patients with MPM was retrospectively reviewed to investigate clinical and histopathological features of first and subsequent melanomas. Methods Patients with MPM who were diagnosed at our Department (1985–2011) and who attended at least a follow‐up control yearly were identified. Results The number of nevi was <10, 10–50 and >50 in 8.7%, 41% and 50.3% of patients respectively. Histopathological dysplastic nevi have been diagnosed in 105 patients. During a median follow‐up of 58 months, 159 (81.9%), 24 (12.3%), 7 (3.6%) and 4 (2%) patients developed 2, 3, 4 and ≥5 melanomas, respectively. The median time to second primary melanoma was 45 months. The second primary melanoma was diagnosed within 1‐year and after 5‐year from the first melanoma in 36.6% and 17.3% of patients respectively. First and second primary melanomas were in situ in 41 (21%) and 104 (54%) patients respectively (P < 0.001). Among patients with ≥2 invasive melanomas (N = 80), median tumour thickness and ulceration of first and second primaries were 0.91 and 0.44 mm (P < 0.001), and 32% and 7.7% (P = 0.001) respectively. Conclusions Subsequent melanomas occurred within 1‐year from the appearance of the first melanoma in 36% of patients with MPM, while a late melanoma diagnosis was detected in 17% of cases. Second primary melanoma had favourable histopathological features. Our findings support long‐term skin surveillance to detect subsequent melanomas at an early stage.